2006
DOI: 10.1158/1055-9965.epi-06-0467
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Investigation of Height and Prostate Cancer Risk

Abstract: Greater adult height, which reflects a combination of early nutrition, exposure to androgens, growth hormones, and other factors during growth and development, as well as heredity, has been associated with increased prostate cancer risk in several observational studies, but findings have been inconsistent. We examined this relationship in the AlphaTocopherol, Beta-Carotene Cancer Prevention Study cohort. At baseline, 29,119 Finnish male smokers 50 to 69 years old had height and weight measured by trained perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…These findings are in agreement with cohort studies [35,36] and other case-control studies [37][38][39] but are in contrast to other studies [40][41][42][43][44] in which increased risk of disease among taller men is suggested. A meta-analysis of cohort and case-control studies suggested a weak positive association with prostate cancer.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in agreement with cohort studies [35,36] and other case-control studies [37][38][39] but are in contrast to other studies [40][41][42][43][44] in which increased risk of disease among taller men is suggested. A meta-analysis of cohort and case-control studies suggested a weak positive association with prostate cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Four studies analyzing five cohorts [7,51,52,58] reported a positive association between fatal prostate cancer and height, with RRs ranging from 1.1 to 2.6 for comparison of the highest to the lowest category. These results are consistent with ours, although the confidence intervals around our risk estimates were wide.…”
Section: Discussionmentioning
confidence: 99%
“…More than 30 prospective and 27 case -control studies have examined height and overall prostate cancer risk (Macinnis and English, 2006;Zuccolo et al, 2008), but findings are mixed; some studies showed a positive association (Le Marchand et al, 1994;Andersson et al, 1997;Giovannucci et al, 1997;Hebert et al, 1997;Rodriguez et al, 2001;Engeland et al, 2003;Cox et al, 2006;Sequoia et al, 2006;Zuccolo et al, 2008), whereas others found no relation (Severson et al, 1988;Cerhan et al, 1997;Veierod et al, 1997;Nilsen and Vatten, 1999;Clarke and Whittemore, 2000;Pischon et al, 2008). Stronger associations were observed for more advanced or fatal prostate cancer among 7 (Andersson et al, 1997;Giovannucci et al, 1997Giovannucci et al, , 2004Rodriguez et al, 2001;Cox et al, 2006;Sequoia et al, 2006;Zuccolo et al, 2008) of the 14 (Le Marchand et al, 1994;Andersson et al, 1997;Giovannucci et al, 1997Giovannucci et al, , 2004Nilsen and Vatten, 1999;Habel et al, 2000;Hsing et al, 2000;Norrish et al, 2000;Rodriguez et al, 2001;Macinnis et al, 2003;Cox et al, 2006;Sequoia et al, 2006;Pischon et al, 2008;Zuccolo et al, 2008) studies ...…”
Section: Discussionmentioning
confidence: 99%